2021
DOI: 10.1039/d1nr05894k
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanocatalysts applied in coupling reactions: a mechanistic insight

Abstract: Well-defined Cu-based nanoparticles represent a valuable catalytic tool for synthesis purposes due to their structural and electronic versatility, requiring thorough mechanistic understanding inputs into their rational design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…For example, in our previous research, we found that some nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs), high-Z gold nanoparticles following intratumoral injection can provide a high local concentration of the agent, reduction of the particle clearance (i.e., renal or hepatic clearance) that increases the bioavailability of nanoparticles and has the effect of radiosensitizer in cancer radiotherapy, which can be used for long-term local anti-tumor therapy [ 112 , 113 ]. As an ideal anti-tumor drug candidate, copper-based nanomaterials have the following advantages: (i) compared with other metals, copper is cheap and rich in content [ 114 ], (ii) copper can induce reactive oxygen species (ROS)-mediated oxidative stress and promote tumor cell apoptosis [ 115 , 116 , 117 ], (iii) it has good biocompatibility, biodegradability, antibacterial properties, and selective cytotoxicity to cancer cells [ 118 ], and (iv) copper-based nanomaterials have less toxic effects on normal cells, fewer side effects, and are safer and more reliable [ 119 ]. Thus, copper-based nanomaterials have attracted more and more attention and have become the current research hotspot.…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%
“…For example, in our previous research, we found that some nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs), high-Z gold nanoparticles following intratumoral injection can provide a high local concentration of the agent, reduction of the particle clearance (i.e., renal or hepatic clearance) that increases the bioavailability of nanoparticles and has the effect of radiosensitizer in cancer radiotherapy, which can be used for long-term local anti-tumor therapy [ 112 , 113 ]. As an ideal anti-tumor drug candidate, copper-based nanomaterials have the following advantages: (i) compared with other metals, copper is cheap and rich in content [ 114 ], (ii) copper can induce reactive oxygen species (ROS)-mediated oxidative stress and promote tumor cell apoptosis [ 115 , 116 , 117 ], (iii) it has good biocompatibility, biodegradability, antibacterial properties, and selective cytotoxicity to cancer cells [ 118 ], and (iv) copper-based nanomaterials have less toxic effects on normal cells, fewer side effects, and are safer and more reliable [ 119 ]. Thus, copper-based nanomaterials have attracted more and more attention and have become the current research hotspot.…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%
“…As a result, the utilization of Cu-based nanostructured materials has increased significantly in a variety of interesting areas such as materials science, synthetic organic chemistry, sensors, catalysis, and energyrelated applications. [7][8][9][10][11] Heterogeneous catalysis has emerged as one of the greatest alternatives for solving the drawbacks of homogeneous catalysis in recent years. 12 Several problems have usually been encountered while using copper nanoparticles (Cu NPs) or Cu salts in reaction systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the utilization of Cu-based nanostructured materials has increased significantly in a variety of interesting areas such as materials science, synthetic organic chemistry, sensors, catalysis, and energy-related applications. 7–11…”
Section: Introductionmentioning
confidence: 99%